A recyclable epoxy for composite wind turbine blades. (3rd July 2019) - Wu, Ming-Sung; Jin, Bo Cheng; Li, Xin; Nutt, Steven
Abstract: Disposal of wind turbine blades, which are generally non-biodegradable and non-recyclable products comprised largely of fiber-reinforced thermoset polymers (FRPs), pose environmental problems when components reach end-of-service-life. Because the global wind turbine market shows steady year-over-year growth, the need for a recycling solution for wind blade FRPs is urgent and growing rapidly. In the present study, recyclable resins, formulated using proprietary epoxy curing agents (Cleavamine ®, Adesso), were charactered and analyzed for processability and recyclability. Protocols for vacuum infusion processing were developed for these recyclable resins. Secondly, laminates of glass fibers and the above epoxy matrices were first produced then recycled, and the properties of recovered fibers were evaluated. Matrix and laminate properties were compared to a benchmark commercial epoxy presently used in commercial wind blades. Results showed that vacuum infusion with the recyclable resins yielded laminates with low void contents and properties comparable to non-recyclable commercial epoxies, and the recovered glass fibers retained surface quality comparable to virgin fibers. Furthermore, results also showed that the recovered matrix residue can be re-used in second-life applications, effectively completing the closed-loop recycling method in this study. Graphical Abstract: